Pragmatic Level Analysis in Translation. Contextual Factors (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Contextual factors play a crucial role in the field of translation as they directly affect the meaning and communicative value of the translated text. Pragmatic analysis involves examining these factors to ensure the translation preserves the intended message, tone, and cultural relevance. This paper explores how various contextual elements, such as linguistic, cultural, situational, and interpersonal contexts, shape the translation process and impact the effectiveness of the final output. Understanding these factors is essential for achieving pragmatic equivalence in translation, where the goal is not merely to reproduce the source text's language but to ensure the same impact and meaning are conveyed to the target audience.